2014
DOI: 10.2169/internalmedicine.53.2564
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related Lung Disease with Organizing Pneumonia Effectively Treated with Azathioprine

Abstract: Immunoglobulin (Ig)-G4-related disease is a multi-organ disease that may affect the lung. We herein describe a patient with IgG4-related lung disease (IgG4-RLD) who was radiologically and pathologically diagnosed with organizing pneumonia. He was successfully treated with a combination of prednisolone (PSL) and azathioprine (AZA), and his clinical course has been uneventful since tapering off PSL. This is a rare case of IgG4-RLD manifesting as organizing pneumonia, and, to our knowledge, this is also the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It has been reported that the combination of immunosuppressants and steroids is effective in treating IgG4-RLD refractory to PSL monotherapy [10], and we are considering the combination of azathioprine and PSL as a future treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the combination of immunosuppressants and steroids is effective in treating IgG4-RLD refractory to PSL monotherapy [10], and we are considering the combination of azathioprine and PSL as a future treatment.…”
Section: Discussionmentioning
confidence: 99%